REMEDIATION OF CADMIUM-CONTAMINATED SOIL USING BIOCHAR AND ITS IMPACT ON WHEAT GERMINATION AND GROWTH (Journal of Medical & Health Sciences Review, 2025)
Heavy metal contamination, particularly cadmium (Cd), poses a severe threat to crop productivity and food safety due to its toxicity and non-biodegradable nature. This study aimed to assess the role of cotton stick biochar (CSB) in mitigating cadmium toxicity in soil and its impact on the germination, growth, and physiological responses of wheat (Triticum aestivum L.). A controlled pot experiment was conducted using soil artificially spiked with cadmium at 0, 4, and 8 mg kg⁻¹ and amended with CSB at 0%, 1%, and 2% (w/w). Results revealed that cadmium stress significantly reduced wheat germination percentage, shoot and root biomass, photosynthetic rate, stomatal conductance, and increased cadmium accumulation in plant tissues. However, the application of 2% CSB markedly improved germination (up to 88%), shoot and root growth, physiological parameters, and reduced cadmium uptake by up to 80% in shoots and 71% in roots. Furthermore, CSB application significantly enhanced soil organic carbon and cation exchange capacity while decreasing available soil cadmium levels. The study demonstrates that CSB is a cost-effective and eco-friendly soil amendment for reducing cadmium bioavailability, improving soil health, and supporting sustainable wheat cultivation under metal-stressed conditions.